PENGARUH MODEL PEMBELAJARAN PJBL BERBANTUAN MEDIA GAMES ENGKLEK TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN PAGERJAYA - Riva Fauziah; Agus Saeful Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Excellent education can be created from a good learning process. Teachers are one of the main factors in determining the quality of optimal learning. Good lesson planning and infrastructure in the form of learning media can help create enjoyable and meaningful learning experiences. This research aims to determine the effect of applying the project-based learning (PjBL) model assisted by the Engklek game media on the concept comprehension abilities of fourth-grade students at SDN Pagerjaya. This research is a quantitative experimental study with a pre-experiment one group pretest-posttest design. The instrument used is an essay test adjusted to the concept comprehension indicators and the material selected by the researcher. The data obtained were then analyzed using normality and homogeneity tests. After the data were found to be normal and homogeneous, hypothesis testing was continued with a paired sample t-test using IBM SPSS 25. Based on the hypothesis test, a sig. (2-tailed) value of 0.000 was obtained. The significant value obtained was less than 0.05 (sig < 0.05), which means that there is an effect of the PjBL learning model assisted by the Engklek game media on the concept comprehension abilities in mathematics for fourth-grade students at SDN Pagerjaya.